Streptozotocin induced oxidative stress, innate immune system responses and behavioral abnormalities in male mice. (6th January 2017) - Amiri, Shayan; Haj-Mirzaian, Arya; Momeny, Majid; Amini-Khoei, Hossein; Rahimi-Balaei, Maryam; Poursaman, Simin; Rastegar, Mojgan; Nikoui, Vahid; Mokhtari, Tahmineh; Ghazi-Khansari, Mahmoud; Hosseini, Mir-Jamal
Highlights: ICV administration of STZ induced behavioral abnormalities in mice after 24 h. These effects were associated with abnormal mitochondrial function in the hippocampus. STZ treatment increased the expression of innate immunity genes in the hippocampus. Sterile inflammatory responses may play a role in the behavioral effects of STZ. Abstract: Recent evidence indicates the involvement of inflammatory factors and mitochondrial dysfunction in the etiology of psychiatric disorders such as anxiety and depression. To investigate the possible role of mitochondrial-induced sterile inflammation in the co-occurrence of anxiety and depression, in this study, we treated adult male mice with the intracerebroventricular (i.c.v.) infusion of a single low dose of streptozotocin (STZ, 0.2 mg/mouse). Using valid and qualified behavioral tests for the assessment of depressive and anxiety-like behaviors, we showed that STZ-treated mice exhibited behaviors relevant to anxiety and depression 24 h following STZ treatment. We observed that the co-occurrence of anxiety and depressive-like behaviors in animals were associated with abnormal mitochondrial function, nitric oxide overproduction and, the increased activity of cytosolic phospholipase A2 (cPLA2 ) in the hippocampus. Further, STZ-treated mice had a significant upregulation of genes associated with the innate immune system such as toll-like receptors 2 and 4. Pathological evaluations showed no sign of neurodegeneration in the hippocampus of STZ-treated mice. Results of this study revealed that behavioral abnormalities provoked by STZ, as a cytotoxic agent that targets mitochondria and energy metabolism, are associated with abnormal mitochondrial activity and, consequently the initiation of innate-inflammatory responses in the hippocampus. Our findings highlight the role of mitochondria and innate immunity in the formation of sterile inflammation and behaviors relevant to anxiety and depression. Also, we have shown that STZ injection (i.c.v.) might be an animal model for depression and anxiety disorders based on sterile inflammation.